Social work practice in the criminal justice system - Patterson, George T. (Routledge, Taylor & Francis Group, 2020)
"Social Work Practice in the Criminal Justice System presents an overview of the criminal justice system for social workers, exploring the networks and institutions which comprise it. Integrating social work ethics and a commitment to social justice, this textbook explores social work practice roles to address social problems within the criminal justice system and promotes the development of knowledge, skills, and critical reflection in this increasingly important area of practice. In addition to covering the four key areas for social work practice - law enforcement, courts, corrections, and legislation, it covers police social work and forensic social work. This second edition has been updated to include: The opioid crisis and opioid courts Separate chapters describing special populations and contemporary issues in the criminal justice system. Expanded criminal justice perspectives and theoretical frameworks. Examining the challenges and opportunities of social work practice in the criminal justice system, this is the ideal text for social work instructors, students, and practitioners working with or within the criminal justice system. Each chapter includes a summary of social work practice implications, key terms, and suggestions for further reading"--